Family Patterns In The Context Of International Migration: Evidence From Families Of International Migrants In Lagos, Nigeria - Oyekanmi, Felicia A. D.; Eborka, Kennedy; Temilola, Olusegun (Advances in Social Sciences Research Journal, 2017)
Migration is generally conceived of as the movement of people from one place to another involving change of usual residence. When the movement is from one country to another, it is international migration; when it is within the country, it is referred to as internal migration. The focus of this paper is international migration involving the movements of Nigerians to other countries. Migration tends to create a disruption in social relationships and networks that have existed over the years. It has been theorized that the longer the duration of stay by the migrating member, the more permanent will be the disruption of existing family pattern and relationship. Some studies on international migration in sub-Saharan Africa appear to concentrate more on the issues of “brain-drain” and social differentiation between migrants’ and non-migrants’ households. This paper examine dthe influence of international migration on family patterns. The study’s specific objectives were to investigate the relationship between international migration and the role of migrants in family’s decision-making process; attainment of desired family size; family headship; and childrearing among families of international migrants in Lagos, The study adopted the non-experimental research design. A sample size of six hundred respondents was drawn from six hundred households with families members living outside Nigeria. The study locations were Eti-Osa and Kosofe Local Government Areas in Lagos State. Our findings indicate that there is no relationship between duration of travel of spouses and the number of children born by the respondents. One could speculate that the desired number of children is usually born before the spouses stay away from this country. The absent family members are usually consulted before important family decisions are made because of the former’s financial strength or birth ranking/position compared to the respondents.